Interactive Effect of Gender and Self-Efficacy on Mathematics Achievement among Students with Mild Intellectual Disability in Calabar Education in Cross River State of Nigeria: Implications for Inclusive Education - Ibok, Ekpenyong Effiong; Ogar, Raymond Ogbebe; Olofu, Paul Agbade; Anam, Blessing Bassey; Bessong, Columbus Deku; Odok, Edmond Asu; Bessong, Napoleon Osang; Amos, Paul Imeh; Ewa, James Abua; Obeten, Amos William; Patrick, Elizabeth Odije; Masor, Grace Ukpabio; et al. (Journal of Intellectual Disability - Diagnosis and Treatment, 2025)
Background: Due to the poor academic achievement of identified SS1 students with mild intellectual disabilities in public secondary schools, this research investigates how gender interacts with self-efficacy regarding mathematics achievement. The goal is to improve these students' academic achievement in mathematics. Studies on the interactive effects of gender and self-efficacy on mathematics achievement in Nigeria are scarce. Objective: This paper examines the interactive effect of gender and self-efficacy on the mathematics achievement of SS1 students with mild intellectual disabilities in the Calabar Education Zone of Cross River State, Nigeria. Methodology: An ex-post facto design was adopted. The study population consisted of 4,031 Senior Secondary (SSI) students with mild intellectual disabilities in the Calabar Education Zone of Cross River State, Nigeria. A sample of 538 students was selected (286 males and 252 females). The instruments used for data collection were the Mathematics Achievement Test (MAT) and a Mathematics Self-Efficacy Rating Scale Questionnaire (MSERSQ). The reliability coefficients were strong (KR-20 = 0.83, Cronbach's Alpha = 0.79) for the MAT and MSERSQ, respectively, indicating good reliability. The study was guided by two research hypotheses. Descriptive statistics were used to describe the collected data, while analysis of covariance and Pearson product-moment correlation were used to test the first hypothesis, and a two-way ANOVA was used to test the second hypothesis. Results: The analysis using Pearson product-moment correlation indicated a significant positive correlation between self-efficacy and mathematics achievement among students with mild intellectual disabilities (r = 0.656, n = 538, p < 0.05). The results of the two-way ANOVA indicated a statistically significant interaction between gender and self-efficacy on mathematics achievement (F = 13.670, n = 538, p = 0.000). This interaction suggests that the influence of self-efficacy on mathematics achievement varies by gender. Specifically, male students (mean = 31.818, SD = 8.320) tended to achieve higher mathematics scores than female students (mean = 27.389, SD = 7.736) did, given their self-efficacy levels. Conclusion: The study found a significant positive relationship between self-efficacy and mathematics achievement, and an interaction between gender and self-efficacy among students with mild intellectual disabilities. Unique Contribution: This paper highlights the unique influence of self-efficacy and the interactive effect of gender and self-efficacy on students with mild intellectual disabilities' mathematics achievement. Recommendation: The government should ensure that sufficient qualified counselors are recruited to help raise students' self-efficacy and guide them accordingly.